Redox-state-regulating enzymes have prognostic value in diabetic endometrial cancer patients: impact of statin use? - Ollila, Elina; Ahtikoski, Anne; Puistola, Ulla; Karihtala, Peeter; Urpilainen, Elina (Frontiers in Oncology, 2024)
Objective The incidence of endometrial cancer is increasing, and oxidative stress has been suggested to play a vital role in its carcinogenesis. Statins have an impact on the cellular redox-state. The aim of this study was to determine the effects of statin use on redox-state regulating enzymes in endometrial cancer in women with type 2 diabetes. Materials and methods This retrospective study consisted of 119 women with type 2 diabetes who were diagnosed with endometrial cancer at Oulu University Hospital in Finland between 2007 and 2014. There were 58 statin users and 61 non-users based on medication use at the time of endometrial cancer diagnosis. The expression of redox-state regulating proteins nuclear factor erythroid 2-related factor 2 (Nrf2) and Kelch-like ECH-associated protein 1 (Keap1) in the tumor samples was assessed immunohistochemically, and manganese superoxide dismutase (MnSOD) levels were measured both immunohistochemically and from serum samples. Results High MnSOD expression predicted better progression-free survival (PFS) in statin non-users in a univariate analysis (p=0.02). There was no statistical difference in overall survival (OS) or PFS between strong and weak expression of Nrf2 and Keap1. After adjusting for stage and statin use, the results were similar. Conclusion Statin non-users with strong MnSOD expression had better PFS compared to statin users which proves that statins have impact on redox-state regulating enzymes. However, these findings are preliminary and require further research.